A Single-Center Study on the Prevalence of Cholesteatoma in People with Central Perforation and Chronic Otitis Media - Khalil Ahmed Orakzai, Imran Khan, Sohail, Ubaid Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: our research discovered that cholesteatoma development was more prevalent in those who have a central perforation and persistent otitis media. Physical exams and meticulous reviews of medical records were performed on 100 people who had chronic otitis media with central perforation. A total of four persons, or 4% of cases, had cholesteatoma. Therefore, it would appear that those who have chronic otitis media with central perforation are more prone to develop cholesteatoma, necessitating the need for surgeons to be aware of this risk in regard to this specific patient group. Aim: This study focused on perforation in the centre of the eardrum caused by chronic otitis media to ascertain the prevalence of cholesteatoma. Methods: Between Duration of study 1st Sep 2022 to 28 February 2023 the ENT department at Lady Reading Hospital conducted the examination. In-depth otoscopic exams and detailed history-taking were performed on 100 consecutive patients with central perforation and persistent otitis media for the study. After the data were processed and categorised, cholesteroleatoma was assessed. Results: Four percent of the 100 individuals had cholesteatoma, whereas the other 96 had no symptoms of the condition. Conclusion: This research demonstrates that those with persistent otitis media and central perforation often get cholesteatoma. Therefore, surgeons must be aware of the potential for cholesteatoma in this particular patient group. To choose the optimal course of treatment for these individuals, further study is required. Keywords: Central perforation, cholesteatoma, and chronic otitis media